LAST BIG CORPORATE SCANDALS IN BRAZIL: Why Investors did not see it in the Annual Reports? - Barros, Arthur do Nascimento Ferreira; Rodrigues, Raimundo Nonato; Miranda, Luiz Carlos; Santos, Milena Rayane Lopes dos (Revista Mineira de Contabilidade, 2020)
This paper measures the level of information disclosure in the fight against corruption in sustainable reports disclosed by companies that participated in the last major corruption scandals in Brazil among 2013 to 2016 (Petrobras S.A., Odebrecht Organization, Brasil Foods S.A. and JBS S.A.); therefore, a not probabilistic sample was chosen. Content analysis through Novethic/SCPC survey (2006) was used to measure the level of disclosure and, among the results, the primary fact observed is that most of these companies exposed to corruption scandals did not modify their level of disclosed information in the fight against corruption, contradicting what was expected in a way that those companies which had higher levels of disclosure before the scandals continued following that path. Those results also revealed that information related to internal organization and a number of departments created to combat corruption were the most disclosed by the studied companies, indicating that these companies used of organized hypocrisy, that is, when the speech on their reports does not match with what is really done. This means that ethics committees created to diminish corruption, reporting systems, strict procedures related to contracting suppliers and other business partners, combined with other actions that encourage the implementation of anti-corruption training and systems were the most disclosed by the studied companies Since information about partnerships with nongovernmental entities and other organizations that have an interest in combating to this type of behavior were the least reported, the results showed off that it is required to look carefully to what is really happening and what it is disclosed by the companies’ reports.